2020
DOI: 10.7759/cureus.10938
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Personal Opportunity Costs of Medical Student Preparation for the United States Medical Licensing Examination Step 1 Exam: A Single-Center Study

Abstract: Cortes-Penfield et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…The most stressful aspects of medical training include preparing for exams and acquiring medical skills, which can lead to high levels of anxiety among medical students [ 24 , 25 ]. Confirming the previous data, most medical students at a United States (US) medical school attributed poor wellness to the United States Medical Licensing Examination (USMLE) preparation process [ 26 ]. Thus, medical students who prepare for exams for postgraduate medical education are at stake regarding the consequences of poor mental wellness: depression, anxiety, burnout, low attention, medical errors, and negligence [ 14 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 60%
“…The most stressful aspects of medical training include preparing for exams and acquiring medical skills, which can lead to high levels of anxiety among medical students [ 24 , 25 ]. Confirming the previous data, most medical students at a United States (US) medical school attributed poor wellness to the United States Medical Licensing Examination (USMLE) preparation process [ 26 ]. Thus, medical students who prepare for exams for postgraduate medical education are at stake regarding the consequences of poor mental wellness: depression, anxiety, burnout, low attention, medical errors, and negligence [ 14 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 60%
“…The 3 studies that explored when students should begin studying for an NLE found that starting farther in advance of Step 1 or COMLEX 1 was associated with higher scores. 48,61,74 However, among medical students, more time overall spent in dedicated exam preparation was not associated with higher Step 1 scores when overall time was estimated to include time before dedicated preparation, 52,67 hours per day studying during the dedicated preparation period, 48,51,71 or length of the dedicated preparation period. 48,51,72 Two studies found that fewer days spent in dedicated preparation was associated with higher…”
Section: Resultsmentioning
confidence: 87%
“…Of the 29 preparation studies, 37,47–74 23 (79%) focused only on Step 1, 4 (14%) on Step 2, 1 (3%) on COMLEX 1, and 1 (3%) on both Step 1 and COMLEX 1. Of all preparation studies, 25 (86%) were done at a single institution, and 17 (59%) used surveys, 1 of which surveyed oral and maxillofacial surgery MD residency program directors about their residents’ preparation habits over a 10-year period.…”
Section: Resultsmentioning
confidence: 99%
“…5, 6). UCISOM students used similar physiologyrelated study materials reported by other pre-clerkship programs [28]. More MS2 students reported using third-party resources as their primary tool for learning compared to the MS1 class (Fig.…”
Section: Discussionmentioning
confidence: 87%